Analysis of Government Policy on Data Collection and Recording of Population Documents as An Implementation of The Principle of Legal Certainty - Emmi Rahmiwita Nasution; Ernawati Manurung (Westscience Press, 2024)
The government's efforts in collecting data and recording population documents have the aim of making the policy to ensure legal certainty for citizens and to make it easier for the public to fulfill their interests. Civil registration is part of the overall population administration system which consists of population registration and civil registration sub-systems. Documents issued by institutions/agencies that handle various public affairs and interests certainly cannot be separated from a series of administrative processes which will ultimately be stored/stored in an archive/data file. The issue raised in this research is how government policies regarding Population Data Collection and Recording can provide legal certainty for all Indonesian people. Based on the provisions for recording names as stipulated in Minister of Home Affairs Regulation Number 73 of 2022 concerning Recording Names in Population Documents, the name recording is carried out on the birth certificate in the event that the resident experiences an important event regarding the birth of a child, so the name recording is carried out on the child's birth certificate in the family. or residents concerned. The aim is to know and understand legal certainty regarding data collection and recording of population documents so that it will provide legal protection. To answer this problem, a normative research type research method was used, namely research using legal materials in the form of regulations, books, scientific articles related to data collection and recording of population documents. The results of this research provide confidence that the existence of data collection and recording of population documents has indeed provided legal certainty for the population of the Republic of Indonesia.